2003
DOI: 10.1024/0300-9831.73.6.447
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Protein Intake on Nitrogen Fractions of Human Milk

Abstract: This study shows that when protein requirements are met and there are no remarkable differences between intakes and requirements, there are no repercussions in nitrogen fractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 0 publications
1
21
0
2
Order By: Relevance
“…We found no evidence for associations between intake of any maternal dietary macronutrient and milk composition in this sample. This is consistent with past studies, which show that milk macronutrient composition appears to be primarily independent of maternal dietary intake (Boniglia et al, 2003;Forsum and Lonnerdal, 1980;Mohammad et al, 2009;Rakiciog lu et al, 2006) even under conditions of maternal malnutrition (Hambraeus et al, 1978;Jelliffe and Jelliffe, 1978a;Lonnerdal et al, 1976;Villalpando et al, 1992). This absence of an effect of maternal diet is evident in both observational studies and experimental designs in which nutritional supplements were shown to result in minimal or negligible changes to milk macronutrients (Prentice et al, 1983).…”
Section: Discussionsupporting
confidence: 91%
“…We found no evidence for associations between intake of any maternal dietary macronutrient and milk composition in this sample. This is consistent with past studies, which show that milk macronutrient composition appears to be primarily independent of maternal dietary intake (Boniglia et al, 2003;Forsum and Lonnerdal, 1980;Mohammad et al, 2009;Rakiciog lu et al, 2006) even under conditions of maternal malnutrition (Hambraeus et al, 1978;Jelliffe and Jelliffe, 1978a;Lonnerdal et al, 1976;Villalpando et al, 1992). This absence of an effect of maternal diet is evident in both observational studies and experimental designs in which nutritional supplements were shown to result in minimal or negligible changes to milk macronutrients (Prentice et al, 1983).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, there were no significant differences between milk lactose and a high-protein diet [ 40 ], or between vegetarian and non-vegetarian diets [ 41 ]. Considering the total protein concentration, studies from Europe and the United States did not report any relationship between milk total protein and maternal intake of animal and vegetable protein [ 42 ]. The variation of total fat concentration in human milk also appears to be independent of maternal diet [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A crossover study from Sweden reported a higher breast-milk total protein content for a maternal diet high in protein than with a low-protein diet (8.83 compared with 7.31 g/d; P , 0.05) (47); in the same study, no difference was observed for lactoferrin and a-lactalbumin in breast milk. Other studies from Europe and the United States did not report any relation between breast-milk total protein and a diet rich in carbohydrate and poor in fat compared with a diet low in carbohydrate and high in fat (49) or a vegetarian compared with a nonvegetarian diet (44) or between breast-milk total protein content and maternal total energy (21), total protein (21), animal protein (21), or vegetable protein (21) intakes.…”
Section: Total Proteinmentioning
confidence: 95%
“…With regard to the breast-milk components of interest, 18 publications examined FA composition (17, 20, 22, 23, 25, 26, 28-31, 35, 38, 41, 44, 46, 50-52), 6 considered total fat (20,28,34,44,48,49), 1 examined cholesterol (48), 1 examined phytosterols (48), 5 considered total protein (21,34,45,47,49), 2 considered total energy (34,49), 2 examined vitamin C (24, 37), 2 examined group B vitamins (24,36), 2 considered vitamin E (19,32), 3 examined zinc (27,33,40), 2 examined total carbohydrates (34,45), 1 considered lactose (49), 3 considered selenium (39,42,43), 2 considered iron (40,45), 1 examined calcium (45), 1 examined magnesium (45), 1 examined potassium (45), and 1 considered oxygen radical absorption capacity (18).…”
Section: Breast-milk Extraction and Compositionmentioning
confidence: 99%